Evaluating the Success of Information Systems based on System Quality, Information Quality and User Satisfaction - Wan Othman, Wan Roslina; Fahmy, Syahrul; Haslinda, Nurul (International Journal of Integrated Engineering, 2022)
Computer Information Systems is vital to organizations including Higher Education Institutions (HEIs) in this era of Big Data and Internet of Things. One example of such system is the Lecturer Information System (LIS). This paper reports the evaluation of LIS success at UC TATI, an HEI in Malaysia based on system quality, information quality and user satisfaction. A survey was administered through the distribution of an online questionnaire to academic faculty members. Results were loaded into the statistical Package for Social Sciences for analysis. An assessment was conducted to test the reliability and validity of the measurements used. Descriptive statistics and reliability analysis were used to analyze the data. Results have demonstrated the feasibility of approach to evaluate IS success. In addition, empirical analysis has indicated positive findings with regards to system quality, information quality, user satisfaction and system success.